Evaluation on performance behaviour of biofuels propelled diesel engine. Issue 1 (31st December 2022) - Manikandan, K.; Ganesh, R.; Chandran, Jishu; Gavaskar, R.
Abstract : The performance characteristics of water-cooled, single-cylinder, four-stroke, diesel engine fuelled with neat Mustard biodiesel and two blends of octanol (Higher Hydrocarbon Alcohol, HHA) and biodiesel, i.e. MUBD80O20 (20%Volume of HHA blended in 80% volume of MUBD) and MUBD60O40 (40%Volume of HHA blended in 60% volume of MUBD) at 2400 rpm for compression ratio 18:1 were investigated. The transesterification process was used for biodiesel production with the presence of the acid catalyst (H2 SO4 ) and methanol. Experimental results exposed that the BSFC reduced and BTE enhanced with HHA blending to mustard biodiesel. Additionally, the diesel engine EGT, when fuelled with MUBD80O20 and MUBD60O40, reduced significantly when compared to base fuel.